2020
DOI: 10.1210/clinem/dgaa500
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Incident Heart Failure in Men and Postmenopausal Women: The Atherosclerosis Risk in Communities Study

Abstract: Context Sex differences exist in heart failure (HF) phenotypes, but there is limited research on the role of sex hormones in HF and its subtypes. Objective To examine the associations of total testosterone, dehydroepiandrosterone sulfate (DHEA-S), and sex hormone binding globulin (SHBG) with incident HF, HF with preserved ejection fraction (HFpEF), and HF with reduced ejection fraction (HFrEF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 45 publications
2
44
1
Order By: Relevance
“…Our results reflect rigorous adjustment for conventional cardiovascular risk factors, which are independently associated with testosterone status. Moreover, our report is in contrast to a very recent report from the ARIC study: the authors found a statistically significant association between testosterone and incident heart failure in a general American community 6 . The HR for heart failure associated with 1‐SD decrease in log‐transformed total testosterone was 1.10 (95% CI: 1.03–1.17) in men and 1.05 (95% CI: 0.99–1.13) in women, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results reflect rigorous adjustment for conventional cardiovascular risk factors, which are independently associated with testosterone status. Moreover, our report is in contrast to a very recent report from the ARIC study: the authors found a statistically significant association between testosterone and incident heart failure in a general American community 6 . The HR for heart failure associated with 1‐SD decrease in log‐transformed total testosterone was 1.10 (95% CI: 1.03–1.17) in men and 1.05 (95% CI: 0.99–1.13) in women, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of these studies suffer limitations like small sample size, limited follow‐up, and incomplete statistical adjustment 5 . Nevertheless, just recently, a new report from the ARIC Study reported a weak, although statistically significant association between testosterone and incident heart failure in a general American community 6 . This borderline finding was only evident in overall analyses and needs to be replicated in further studies and populations 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Ejection fraction measurement information was recorded for events diagnosed as HF by MESA cardiac reviewers. Based on LV ejection fraction (LVEF) (≥50% or <50%), HF was further classified as either HF with preserved ejection fraction or HF with reduced ejection fraction 26,27 …”
Section: Methodsmentioning
confidence: 99%
“…Low levels are associated with an increased risk of morbidity, as well as all-cause mortality and cardiovascular death among the general population. Recently the Atherosclerosis Risk in Communities (ARIC) study was published, which specifically studied the risk for heart failure in both men and women, and showed that lower levels of endogenous testosterone in men, DHEA-sulphate in men, and post-menopausal women were associated with subsequent development of HF [ 84 , 85 , 86 , 87 , 88 ]. Within the group of patients with HF, Jankowska et al and Wehr et al showed that, indeed, below normal androgen levels in HF patients were an independent predictor of mortality [ 79 , 89 ].…”
Section: The Role Of Testosterone In Chronic Heart Failure and Aftmentioning
confidence: 99%